Cosumer Perception Toward Online Banking Services to Build Brand Loyalty: Evidence from Indonesia - Kesa, D D (KnE Social Sciences, 2018)
The competitiveness in banking sector makes bank put a serious effort to give the best service in order to have loyal customers. Forty respondents were contacted and used in this research through random sampling methods. The use of the Internet by banks provides a comfortable, simple and safe transaction. With the existence of internet banking, it helps the customers to have more efficient activity in banking transactions. In addition, internet banking also has a positive impact on the banks as a provider of this service. The t-test result showed that brand loyalty is variable with positive and significant effect on customer satisfaction. The quality service of internet banking variable does influence customer satisfaction positively but not significantly. Through internet banking, each bank hopes to be able to maintain the customers and even be able to increase the number of transactions. Keywords: brand loyalty service quality, Internet banking customer satisfaction